2009
DOI: 10.1002/jmv.21565
|View full text |Cite
|
Sign up to set email alerts
|

Immune activation and antibody responses in non‐progressing elite controller individuals infected with HIV‐1

Abstract: An extremely rare subset of patients infected with HIV-1 designated as "non-progressing elite controllers" appears to be able to maintain stable CD4(+) T-cell counts and a median plasma viremia below the detection limit of current ultrasensitive assays (<50-80 copies/ml of plasma) for >10 years in the absence of antiretroviral therapy. Lymphocyte subsets (CD4(+), CD8(+)), immune activation markers (HLA-DR(+), CD38(+), Beta-2-microglobulin), and HIV-specific antibody responses were longitudinally examined in fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 52 publications
(79 reference statements)
5
29
0
Order By: Relevance
“…All discrepant cases had undetectable viral load, that were identified as recent by the Vironostika S/LS assay but not with the Avidity assay, indicating that viral suppression affects the performance of cross sectional incidence assays based on antibody titer. Similar results were obtained for four long-term non-progressors/elite controllers from Brazil, who gave results compatible with recent infection based on the competitive BED-CEIA assay, whereas only 2 out of 4 were misclassified when using the avidity assay 66 .…”
Section: Final Remarkssupporting
confidence: 75%
“…All discrepant cases had undetectable viral load, that were identified as recent by the Vironostika S/LS assay but not with the Avidity assay, indicating that viral suppression affects the performance of cross sectional incidence assays based on antibody titer. Similar results were obtained for four long-term non-progressors/elite controllers from Brazil, who gave results compatible with recent infection based on the competitive BED-CEIA assay, whereas only 2 out of 4 were misclassified when using the avidity assay 66 .…”
Section: Final Remarkssupporting
confidence: 75%
“…Data from several groups, however, have suggested that cells lacking activation markers are also capable of being infected, and among activated cells there are differences in susceptibility to infection (39)(40)(41)(42)(43). We and others have previously shown considerably higher levels of CD4 + T-cell activation in CP than ES (36,44,45), and activation does not correlate with susceptibility to infection ex vivo in our system (36). To investigate the subset of CD4 + T cells most susceptible to infection, we infected unstimulated CD4 + T cells from uninfected donors using either X4-or R5-tropic virus.…”
Section: Resultsmentioning
confidence: 85%
“…1.5 years) they have elevated levels of immune activation and spontaneous T-cell apoptosis similar to treated HIV-infected subjects or untreated rapid progressors (Ronquillo et al, 2010;Goicoechea et al, 2009). Low levels of virus replication probably explain for the presence of T-cell activation in controllers and progressors earlier in infection and which has been shown to decline over time in controllers, but not in progressors (Bello et al, 2009). …”
Section: Some Evidence Suggests That Ltnps Have Reduced Cd4mentioning
confidence: 99%
“…+ Tcell activation in comparison with subjects with rapid disease progression (Bello et al, 2009;Marchetti et al, 2009). Less CD4 + T-cell immune activation reduces the number of cells susceptible to HIV-1 infection and can potentially lead to a better disease prognosis.…”
Section: Some Evidence Suggests That Ltnps Have Reduced Cd4mentioning
confidence: 99%
See 1 more Smart Citation